(untitled) (Fiep Bulletin - online, 2016)
The obesity is one of the most worrying problems for public health nowadays because of the many problems caused to people’s health. The obesity growth has been alarming, especially in children, extending the problem to the adulthood. The childhood obesity has been the subject of many studies; it has increased intensively and quickly. The family and the school have a key role in preventing childhood obesity, allying a healthy diet and joyful activities to make the kid do some exercises. This study aims to analyze through the literature, if playful activities can contribute to the minimization of childhood obesity in the school environment. The method used in this study is based on an extensive literature related to the subject in the period of 1988 to 2007, in books, articles and websites available on the internet and in magazines. It is considered that the practices of playful exercises are important to the achievement of a better apprenticeship, personal, social and cultural development, and also to a good mental and physical health. Besides, the practice of recreational activities is something very pleasant, and a great device to the child achieves healthier habits.